Analisis Gaya Bahasa dan Makna Lirik Lagu Berpayung Tuhan Karya Nadin Amizah: Kajian Stilistika - Dalimunthe, Miftah Nurul Fathiyya; Nadisa Wiasqi Faza; Welsi Damayanti (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
Songs as a way to channel emotions, feelings and a message, where the emotions, feelings and messages conveyed can sound more beautiful with the use of linguistic styles in it. Just like Nadin Amizah with her song “Berpayung Tuhan” which uses a lot of linguistic styles that make the song so beautiful and has a deep meaning. This study aims to interpret the language style and meaning contained in Nadin Amizah's song “Berpayung Tuhan” using qualitative research methods. The results of this study found that the song “Berpayung Tuhan” means about a strong relationship between two individuals both physically and emotionally so that the presence of one of them can provide a sense of security, comfort and bring happiness and also the protection of God, hope, trust and even love that describes the life journey of someone who is loved even though there is a lot of distance between them goodness, happiness and peace will continue to remain and grow wherever they are. Keywords:Meaning, Song, Linguistic styles